Gestión de los beneficios sociales en la empresa center drive de la ciudad de Babahoyo - García Gómez, Edison Eduardo (2022)
The present case study consists of determining the fulfillment of the social benefits in the company Center Drive, towards the collaborators, these types of benefits, fulfill a fundamental role in any organization, being considered a strategic tool, because it allows to increase the productivity and the loyalty of its employees, it is worth mentioning that these are not related to salary or overtime, its objective is to be able to improve the quality of life of workers, improving some of their present needs, in addition to offering these benefits the growth of the company positively influences. It is important that companies grant these social benefits, which generates happiness to the personnel that works in the company and therefore this translates into a commitment and a better performance in the activities that are carried out within the entity, they also allow to reduce the turnover in the workforce, very important for a company to obtain the maximum benefit that the experience of a worker in a business gives it over the years. To obtain information, the deductive method was used, which allowed obtaining as an information collection technique the execution of a survey, directed at the workers of the Center Drive company, in order to determine and know if these benefits are met.